Exploring the historicism and theatrical aesthetics in Èỵọ̀ masquerade festival - Ọlápéju, Shuaib Shadiat; Yétúndé, Lẹ́wú Mary Àlàbá (Penerbit Universiti Kebangsaan Malaysia, 2020)
The “AdámúÒrìṣà” festival also known as Ẹ̀yò ̣masquerade festival, has been acknowledged since time immemorial as a unique religious festival celebrated among the citizens of Lagos State, South-west Nigeria by many scholars, historians and anthropologists. During the festival, the final funeral rites of kings, chiefs and some notable citizens who had made positive contributions to the state were also commemorated. In view of this, this paper adopted historical and descriptive methods through primary and secondary data drawn from interviews with Èỵ ò ̣custodians, library and internet materials to examine the history as well as ritualistic and theatrical constituents of the masquerade performance. It discovered that despite its spiritual and religious significances, its popularity had increased in leaps and bounds over the years in a cosmopolitan setting because of the artistic and aesthetic appeal it has on the ever increasing spectators due to its theatrical attributes. This way, the Èỵ ò ̣ masquerade festival has become one of the platforms that showcased the rich cultural heritage of Nigerians in general and Lagos State in particular. The paper concludes that the Èỵ ọ̀ masquerade festival is serving very useful religious, cultural, entertainment and economic purposes and should therefore be expanded and promoted to further boost cultural rejuvenation and tourism among others.